The genetic council’s bioethic aspects in the human genome project’s era - Santos Alcántara, Manuel J. (Acta Bioethica, 2004)
The Human Genome Project has had a significant impact in Medicine. Genomic Medicine is becoming more preventive than curative. The knowledge obtained by the Human Genome Project has allowed the development of genetic diagnostic tests for patients already affected (symptomatic diagnosis) or patients who will develop the condition in the future (presymptomatic diagnosis). These genetic tests may also be used in prenatal or preimplantational genetic diagnosis. Genetic counseling has a central role in the Genomic Medicine. This paper deals with the Human Genome Project and Genetic counseling from a bioethical point of view.